Investigating soil nitrogen dynamics in natural, invaded and cleared fynbos riparaian ecotones and implications for riparian functioning - Fourie, Marno (Stellenbosch : Stellenbosch University, 2014)
Thesis (MScConsEcol)--Stellenbosch University, 2014.